Pain, alcohol use disorders and risky patterns of drinking among people with chronic non-cancer pain receiving long-term opioid therapy. (1st May 2016) - Larance, Briony; Campbell, Gabrielle; Peacock, Amy; Nielsen, Suzanne; Bruno, Raimondo; Hall, Wayne; Lintzeris, Nicholas; Cohen, Milton; Degenhardt, Louisa
Highlights: We examined alcohol use among people using opioids for chronic non-cancer pain. One-third had a lifetime alcohol use disorder, with riskier drinking among males. Both abstinence and risky drinking independently predicted poorer pain outcomes. Alcohol interventions might positively impact on pain outcomes in this group. Abstract: Background: The utilisation of pharmaceutical opioids has increased internationally, and there is evidence of increasing risky alcohol consumption with ageing. This study examines the patterns and correlates of risky drinking among people with chronic non-cancer pain (CNCP) prescribed opioids, and the associations between alcohol consumption and pain. Methods: The Pain and Opioids IN Treatment cohort comprises 1514 people in Australia prescribed pharmaceutical opioids for CNCP. Participants reported lifetime, past year and past month alcohol use, as well as mental and physical health, other substance use, pain characteristics, and current opioid dose. Results: Less than one-tenth of the sample were ' lifetime abstainers ' (7%); 34% were ' former drinkers '; 34% were ' non - risky drinkers ' (i.e., past 12 month use ≤4 standard drinks); 16% were ' occasional risky drinkers '; and 8% were ' regular risky drinkers ' (i.e., ≥weekly use of >4 standard drinks). Males reported greater levels of alcohol use, and a third (33%) of the total sample reported a lifetime alcohol use disorder. Controlling for demographics, mental health, physical health and substance use disorder history, 'former drinkers' (cf. ' non-risky drinkers ') reported higher pain severity and interference ratings, and lower pain coping. 'Occasional risky drinkers' and 'regular risky drinkers' (cf. ' non-risky drinkers ') reported higher levels of pain interference. Conclusions: Among people with CNCP, those who abstained from alcohol or drank at risky levels reported poorer pain outcomes compared with moderate drinkers. Early identification and intervention for risky drinking among people is critical, particularly given the risks associated with co-administration of alcohol and opioids.